2015
DOI: 10.1002/jor.22851
|View full text |Cite
|
Sign up to set email alerts
|

Concept of variable angle locking-evolution and mechanical evaluation of a recent technology

Abstract: Applications for fracture-adapted screw positioning offered by variable angle locking screws are increasing. The locking strength of the variable angle locking mechanism at different insertion angles was compared to conventional fixed angle locking screws. Stainless steel (S) and titanium (Ti) variable and fixed angle 2.4 mm locking screws, inserted at different inclinations (0˚À15˚), and locked at 0.8 Nm were subjected to a load-to-failure test. Ultimate failure moment at the screw-head interface and failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…The design of recent locked plating systems provides the opportunity for poly-axial screw placement. While this enhances the ability to capture individual fracture fragments by placing the screws accordingly, it involves the risk of earlier screw loosening [27]. The findings from this study suggest that the poly-axial mechanism has no biomechanical disadvantages in terms of construct stiffness and fatigue failure.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The design of recent locked plating systems provides the opportunity for poly-axial screw placement. While this enhances the ability to capture individual fracture fragments by placing the screws accordingly, it involves the risk of earlier screw loosening [27]. The findings from this study suggest that the poly-axial mechanism has no biomechanical disadvantages in terms of construct stiffness and fatigue failure.…”
Section: Discussionmentioning
confidence: 77%
“…The findings from this study suggest that the poly-axial mechanism has no biomechanical disadvantages in terms of construct stiffness and fatigue failure. Previous studies even suggested that poly-axial locking mechanisms are more forgiving in terms of screw stability for deviation from correct screw inclination than fixed angle locking mechanisms [27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a significant drop of the removal torque in some groups after cyclic loading with significance related to small standard deviations, over 84% of the initial removal torque of fixed, and variable angle locking screws persisted. A loosening of the locked head would implicit a nearly complete drop of the removal torque, since loosened head threads provide no torque resistance during unscrewing …”
Section: Discussionmentioning
confidence: 99%
“…For this study, a modification of a previously published test setup was used . Stainless steel and Titanium‐Aluminum‐Niobium (TiAl6Nb7) 2.4‐mm, variable angle locking screws of 30 mm length (ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation